Patients With Obsessive-Compulsive Disorder Exhibit Deficits in Consummatory but Not Anticipatory Pleasure - Li, Sihui; Zhang, Yi; Fan, Jie; Liu, Wanting; Gan, Jun; He, Jing; Yi, Jinyao; Tan, Changliang; Zhu, Xiongzhao (Frontiers in Psychology, 2019)
Background: Reward dysfunctions have been reported in Obsessive-compulsive disorder (OCD), which implicates a high possibility of anhedonia for this disease. However, several components of anhedonia, such as consummatory and anticipatory pleasure, has not been substantially studied in OCD patients. Methods: The Chinese version of the Temporal Experience of Pleasure Scale (CV-TEPS) was used to evaluate both the consummatory and anticipatory pleasure in 130 OCD patients, 89 major depressive disorder (MDD) patients, and 95 healthy controls (HCs). The Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) and the Beck Depression Inventory (BDI) were scored for assessing the severity of obsessive and compulsive symptoms and depressive symptoms, respectively. Analyses of covariance (ANCOVA) were used to compare the differences of anhedonia among the three groups with the severity of depression controlled. Regression analyses were also used to analyze the relationship between consummatory and anticipatory pleasure and clinical variables in OCD patients. Results: After controlling for the effect of depression, there were significant differences in TEPS scores among the three groups (p < 0.05). Compared with HCs, OCD patients had lower scores on the consummatory subscale, but not the anticipatory subscale, of the TEPS. MDD patients had lower scores on both the consummatory and anticipatory subscales than HCs. Conclusions: OCD patients exhibit deficits in consummatory but not anticipatory pleasure, which is distinct from MDD patients.